Women's activism in Latin America and the Caribbean : engendering social justice, democratizing citizenship - Maier, Elizabeth; Lebon, Nathalie (Rutgers University Press ; El Colegio de la Frontera Norte A.C., 2010)
Brings together a group of interdisciplinary scholars who analyze and document the diversity, vibrancy, and effectiveness of women's experiences and organizing in Latin America and the Caribbean during the past four decades. Most of the expressions of collective agency are analyzed in this book with the context of the neoliberal model of globalization that has seriously affected most Latin American and Caribbean women's lives in multiple ways. Contributors explore the emergence of the area's feminist movement, dictatorships of the 1970s, the Central American uprisings, the urban, grassroots organizing for better living conditions, and finally, the turn toward public policy and formal political involvement and the alternative globalization movement. Geared toward bridging cultural realities, this volume represents womens transformations, challenges, and hopes, while considering the analytical tools needed to dissect the realities, understand the alternatives, and promote gender democracy--From publisher description.